Low power flip-flop circuits for high-performance systems - Chua, Yong Kiang. (2010)
The increasing demand of portable applications motivates the research on low power and high speed circuits. The tighter timing constraint as well as the low power requirement has made the timing elements such as latches and flip-flop critical to the performance of a digital system.